Cardiovascular comorbidity and cardiovascular risk factors in patients with chronic inflammatory skin diseases: A case-control study utilising a population-based administrative database (Italian Journal of Public Health, 2008)
Background: : Psoriasis (PSO) and atopic eczema (AE) are chronic inflammatory disorders that primarily affect the skin. Data on cardiovascular comorbidity in PSO is scarce, and studies on the association of cardiovascular disease/cardiovascular risk factors and AE are missing. Methods: We performed two separate case-control studies for PSO and AE utilising an administrative health care database including approximately 250,000 individuals from Germany. Cases with AE (n=6,296) and cases with PSO (n=3,156) were individually-matched (1:1) to controls with the same age and sex. Odds ratios (OR) and 95% confidence intervals (95%CI) were calculated based on the observed prevalences of cardiovascular morbidity among cases and controls.Results: Patients with AE had a higher risk of obesity (OR,95%CI 1.24, 1.07-1.44). None of the other cardiovascular risk factors or diseases studied was associated with AE. PSO was significantly associated with hypertension (OR,95%CI 1.45, 1.27-1.66), diabetes mellitus type-2 (OR,95%CI 1.35, 1.13-1.61), obesity (OR,95%CI 1.58, 1.34-1.85), dyslipidemia (OR,95%CI 1.42, 1.14-1.77), and atherosclerosis (OR,95%CI 1.81, 1.37-2.41). Despite their unfavorable cardiovascular risk factor profile, patients with PSO were not at increased risk of adverse cardiovascular events (myocardial infarction OR,95%CI 1.14, 0.74-1.77; cerebral apoplexy OR,95%CI 0.94, 0.57-1.55).Conclusions: Chronic inflammation due to AE does not appear to cause adverse cardiovascular comorbidities. In contrast, PSO is associated with an adverse cardiovascular risk factor profile, but this does not necessarily appear to translate into a higher risk for cardiovascular events. This study does not rule out that specific treatments for AE or PSO modify the risk of cardiovascular disease.
Keywords: Atopic dermatitis; cardiovascular diseases; case-control study; hypertension; obesity; psoriasis